(untitled) (Experimental biology, 2023)
Balkash Lake is one of the largest reservoirs in South-Eastern Kazakhstan, taking the 2nd place in terms of area after the Caspian Sea. The current environmental problems are damaging the ichthyofauna of the lake, where many populations of commercial fish species are significantly affected. Fish, being part of an ecosystem, are able to show adaptive properties by changing their biological (species) characteristics in response to environmental changes. With the increase in pollution of aquatic ecosystems, qualitative changes in the external and internal structure of fish occur. The chosen object of study, carp (Cyprinus carpio), is a good example of manifestations of adaptations in response to changes in the quality of the habitat. The study of the variability of morphometric traits in fish is an important direction in identifying anomalies and monitoring the general health of fish. In this regard, we studied 28 plastic features and 16 meristic (countable) features, as well as the presence of deviations in the appearance of the carp (external malformations). The study using the method of multivariate statistical analysis made it possible to determine the load and direction of changes in individual signs of carp. Based on the results of morphological studies, the phenotypic plasticity of carp correlates with the negative environmental conditions of the western part of Lake Balkash.